From welfare to work: The health and material well-being effects of long-term employment subsidies in Germany - Nadja Bömmel; Mustafa Coban; Zein Kasrin; Maximilian Schiele; Claudia Wenzig; Joachim Wolff; Cordula Zabel (International Journal of Social Welfare, 2024)
This paper analyses effects of subsidised, predominantly non-standard, employment within the German labour market programme `participation in the labour market' for long-term welfare recipients on their health satisfaction, health-based quality of life, satisfaction with standard of living and households' actual ownership of important goods (e.g., car or new clothes) or the lack thereof due to financial reasons. We differentiated subgroups by health, age and working hours. Data for participants and non-participants (but entitled to welfare benefits) stem from the first two waves (2020/2021) of the panel survey `Quality of Life and Social Participation'. To identify causal effects, we employed matching methods based on administrative and survey data. Our findings show that 1 and 20.167emyears after programme start, participation had significant positive effects on all indicators of health and standard of living. Thus, for the programme's focus group, subsidised employment, even if non-standard, can contribute to improving health and material well-being.
Keywords: 330; active labour market policy (ALMP); health; long-term unemployment; matching analysis; material resources; non-standard work; social participation; welfare benefits